2018
DOI: 10.1029/2017ja025125
|View full text |Cite
|
Sign up to set email alerts
|

CESE‐HLL Magnetic Field‐Driven Modeling of the Background Solar Wind During Year 2008

Abstract: In this paper, the CESE-HLL three-dimensional magnetohydrodynamic solar wind model is first modified to be able to work in a corona-heliosphere integrated approach and then used to simulate the evolution of solar wind from the solar surface to the Earth's orbit during year 2008. Here high-cadence photospheric magnetic field data are used to drive the model at the solar surface via the projected normal characteristic boundary equations. The simulated results are analyzed and quantitatively evaluated by comparin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 96 publications
1
5
0
Order By: Relevance
“…The maximum-time (minimum-time) level of f au has systematically decreased from cycle 22 maximum to cycle 24 maximum (from mid-1980s to mid-2000s, respectively). This long-term decrease of the observed HMF flux density in recent decades is well documented (Smith & Balogh 2008;Lockwood 2013). The same systematic decline is seen in f ss in Figures 2(a) and (b) for all values of r ss from cycle 22 until recently.…”
Section: Long-term Evolution Of the Source Surface Radiussupporting
confidence: 76%
See 1 more Smart Citation
“…The maximum-time (minimum-time) level of f au has systematically decreased from cycle 22 maximum to cycle 24 maximum (from mid-1980s to mid-2000s, respectively). This long-term decrease of the observed HMF flux density in recent decades is well documented (Smith & Balogh 2008;Lockwood 2013). The same systematic decline is seen in f ss in Figures 2(a) and (b) for all values of r ss from cycle 22 until recently.…”
Section: Long-term Evolution Of the Source Surface Radiussupporting
confidence: 76%
“…Recently, (Koskela et al 2017) showed that the PFSS model reliably produces the HMF sector structure. Moreover, adding horizontal currents (as in the current sheet source surface (CSSS) model; Koskela et al 2019) or using an MHD model (Li & Feng 2018) does not improve the polarity match between the corona and the heliosphere. All these studies indicate that, despite its simplified assumptions (lack of currents and spherical source surface), the PFSS model can well produce the large-scale coronal magnetic field structure, even at different solar activity conditions.…”
Section: Introductionmentioning
confidence: 99%
“…During the declining and minimum phase of solar cycle 23, both PFSS and MHD modeled results driven by GONGb synoptic maps gave satisfying results (e.g., Gressl et al., 2014; Feng et al., 2017; Jian et al., 2016, 2015; Li & Feng, 2018; Li, Feng, & Wei 2020; Li, Feng, Zuo, & Wei 2020; Wiengarten et al., 2014). However, as can be seen here, the GONGb maps do not perform well during the declining phase of solar cycle 24.…”
Section: Summary and Discussionmentioning
confidence: 92%
“…The long-term average polarity match with the CSSS model optimal R cs is 85.6% for a = 0.01 and 0.1, 85.4% for a = 1, and with the PFSS model optimal r ss 85.9%. For comparison, Li & Feng (2018) modelled the corona and heliosphere using a coupled coronal and heliospheric 3D MHD model, and obtained a polarity match of 85.8% in 2008. The polarity match we obtained for 2008 with the CSSS model optimal parameters was 88.2% for a = 0.01, 88.1% for a = 0.1, 88.4% for a = 1, and 87.4% for the PFSS model with the optimal r ss .…”
Section: Discussionmentioning
confidence: 99%